G454(P) Quantity of patient contact with a paediatric diabetes service – is there correlation with HbA1c?. (27th April 2016) - Buston, G; Nicholson, J; Satish, H
Abstract : Objectives: Best Practice Tariff (BPT) guidelines recommend that paediatric patients with diabetes should have a minimum of four MDT clinic appointments, and an additional eight contacts with the diabetes service per year. Trusts must achieve 90% compliance with these targets to receive incentive payments (upto £2988 per child). This audit compares performance in a DGH against these recommendations. It seeks to determine whether there is a correlation between amount of contact with the service and average HbA1c level. Methods: Analysis of a database recording contacts with a total of 159 children between April 2014 and March 2015 (BPT financial year) Results: Of the 159 patients, 21 (13%) were newly diagnosed, 19 (12%) were transitioning to adult services, and one had care shared with another hospital. These were analysed separately. For the remaining children the median total number of contacts per year was 23. The median number of MDT contacts was four per year, and of additional contacts was 18.5 per year. Additional contacts included telephone calls, texts, school visits and home visits. 93% of these children were offered at least four MDT appointments per year, 100% were offered at least eight additional contacts with the service, and 100% had a total of at least 12 contacts. The median HbA1c was 61mmol/mol and 35% of patients had HbA1c <58mmol/mol (i.e. "good" control as per NPDA definitions). There was no correlation between total number of contacts per year and median HbA1c (P = 0.18). However, there was a weak positive correlation (Pearson's rank 0.34) between number of MDT clinic appointments and median HbA1c (P < 0.001). Conclusions/recommendations: Compliance with BPT guidelines was achieved in the majority of cases, although 7% were offered less than four MDT clinic appointments for the year. Patients received on average 11 more contacts per year than the minimum requirement (these were mostly 'additional contacts'). Correlation between MDT contacts and HbA1c suggests that the paediatric diabetes team are recognising patients with poor control and organising additional follow up. More comprehensive routine data collection will allow further analysis of the contacts taking place to ensure quality as well as quantity.